Transduction of the Central Nervous System After Intracerebroventricular Injection of Adeno-Associated Viral Vectors in Neonatal and Juvenile Mice - Gholizadeh, Shervin (Mary Ann Liebert, Inc., 2013)
Several neurodevelopmental and neurodegenerative disorders affecting the central nervous system are potentially treatable via viral vector-mediated gene transfer. Adeno-associated viral (AAV) vectors have been used in clinical trials because of their desirable properties including a high degree of safety, efficacy, and stability. Major factors affecting tropism, expression level, and cell type specificity of AAV-mediated transgenes include encapsidation of different AAV serotypes, promoter selection, and the timing of vector administration. In this study, we evaluated the ability of single-stranded AAV2 vectors pseudotyped with viral capsids from serotype 9 (AAV2/9) to transduce the brain and target gene expression to specific cell types after intracerebroventricular injection into mice. Titer-matched AAV2/9 vectors encoding the enhanced green fluorescent protein (eGFP) reporter, driven by the cytomegalovirus (CMV) promoter, or the neuron-specific synapsin-1 promoter, were injected bilaterally into the lateral ventricles of C57/BL6 mice on postnatal day 5 (neonatal) or 21 (juvenile). Brain sections were analyzed 25 days after injection, using immunocytochemistry and confocal microscopy. eGFP immunohistochemistry after neonatal and juvenile administration of viral vectors revealed transduction throughout the brain including the striatum, hippocampus, cerebral cortex, and cerebellum, but with different patterns of cell-specific gene expression. eGFP expression was seen in astrocytes after treatment on postnatal day 5 with vectors carrying the CMV promoter, expanding the usefulness of AAVs for modeling and treating diseases involving glial cell pathology. In contrast, injection of AAV2/9-CMV-eGFP on postnatal day 21 resulted in preferential transduction of neurons. Administration of AAV2/9-eGFP with the synapsin-1 promoter on either postnatal day 5 or 21 resulted in widespread neuronal transduction. These results outline efficient methods and tools for gene delivery to the nervous system by direct, early postnatal administration of AAV vectors. Our findings highlight the importance of promoter selection and age of administration on the intensity, distribution, and cell type specificity of AAV transduction in the brain.